PALM OIL REPLACEMENT BY KEPAYANG OIL (Pangium edule Reinw) IN DIETS ON THE QUAIL GROWTH PERFORMANCES - Wiwaha Anas Sumadja; A Azis; C. A. Damayanti (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
ABSTRACT Currently, the utilization of palm oil as a feed ingredient competes with human needs; thus, we must explore new sources of oil that may be used as alternative feed. Kepayang oil is a new form of feed oil due to its high content of unsaturated fatty acids, which helps in quail growth. The goal of this investigation is to see how replacing palm oil in rations with kepayang oil affects quail growth. The study used 200 female quail 21 days old, kepayang oil, commercial palm oil, mineral mix, maize meal, fish meal, bran, soy cake, lysine, methionine, and 20 units of the quail's cage